Study on Performance of Single Cylinder Engine Fueled by LPG - Ayob, Md Razali; Mat, Shafizal; Herawan, Safarudin Gazali; Sulaiman, Mohd Yusoff (2011)
In this study, characteristics on single piston spark ignition (SI) internal combustion engine (ICE) operated with unleaded petrol (ULP) and liquid petroleum gas (LPG) has been compared. In particular, torque and horsepower were examined using dynamometer and emission characteristics of harmful gases such as carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxide (NOx) have been examined by using exhaust gas analyzer. In additional the temperature test has been done to identify which fuel can contribute damage on engine component. SI engine fueled by LPG recorded a decrease on torque output up to 10% compared to ULP. However emission measurement showed that the engine fueled by LPG produce 40% less CO, 60% lean CO2 and 20% less NOx emission compared to ULP. However SI engine fueled by LPG require more fuel In reach certain RPM. LPG fuel produce more heat compared to ULP. Measurements also showed that engine fueled by LPG operate at a high temperature.